The Effectiveness of Physics Learning with Blended Learning Models using the Edmodo Application to Improve Students' Critical Thinking Skills - Najib, Nasa; Jatmiko, Budi (International Journal of Active Learning, 2022)
This study aims to describe the effectiveness of learning physics with a blended learning model using the Edmodo application to improve the critical thinking skills of high school students. The sample of this study were students of SMA Negeri 1 Ngronggot which consisted of two classes, namely X MIPA 1 and X MIPA 2, each class totaling 30 students. This research is pre-experimental research with one group pretest-posttest design. Before learning is done, students are given an initial test (pre-test) and after learning, students are given a final test (post-test) with the same material. The collected data was then analyzed using paired t-test, n-gain calculation, and independent t-test. which were analyzed quantitatively. The results showed that there was an increase in students' critical thinking skills scores with an average value of n-gain on the high criteria in each experimental class and there was no difference in the average value of n-gain between the two experimental classes. It can be concluded that learning physics with a blended learning model using the Edmodo application can effectively improve students' critical thinking skills. This research implies that learning physics with a blended learning model using the Edmodo application can be used as an alternative learning model that can be used to improve students' critical thinking skills.